Effect of Nusantara diet feeding with triglyceride glucose index as a measure of insulin resistance in individuals’ metabolic syndrome risk. - Rahma; Bukhari, Agussalim; Aminuddin, Aminuddin; Taslim, Nurpudji A; Rasyid, Haerani; Syauki, Yasmin (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Metabolic syndrome is rising among all age groups due to diets high in fats, common in Indonesia. While these diets can worsen insulin resistance, virgin coconut oil, prominent in the Nusantara diet, may improve it. This study evaluates the impact of the Archipelago Diet on insulin resistance, using the TyG Index, aiming to develop dietary strategies for managing metabolic syndrome. Methods: This study is an experimental study, with a parallel clinical trial, with a pre-posttest randomised design and open trial study to compare insulin resistance from HOMA-IR values between groups. The study subjects were 50 people selected according to the predetermined inclusion and exclusion criteria and then divided into two groups, namely the intervention group and the control group, each consisting of 25 subjects. Results: The results showed that after 2 months of Nusantara diet, there was a decrease in body weight, body mass index (BMI), and abdominal circumference in the intervention group compared to the control group. Specifically, the intervention group experienced a 3.2% decrease in body weight, a 3.1% decrease in BMI, and a 4.2% decrease in abdominal circumference. The control group experienced a 1.1% decrease in body weight, 0.7% decrease in BMI, and 1.1% decrease in abdominal circumference. Conclusion: The Nusantara diet for 2 months showed no significant effect on the TyG Index of individuals at risk of metabolic syndrome.